A polysomnographic study of sleep disruptions in individuals with chronic neck pain. (19th January 2022) - Aldabbas, Mosab M.; Tanwar, Tarushi; Ghrouz, Amer; Iram, Iram; Warren Spence, David; Pandi‐Perumal, Seithikurippu R.; Veqar, Zubia
Summary: Various lines of evidence suggest that a bidirectional relationship exists between poor sleep quality and chronic pain, with each condition tending to promote and exacerbate the other. This has led to the hypothesis that the two conditions may be linked by common underlying mechanisms. It has thus been suggested that inadequate sleep and chronic pain may share neurophysiological and molecular pathways that are similar or overlapping. Some studies based on self‐report measures have tended to support the inference that chronic neck pain may promote sleep disturbance, but this association has not, until now, been investigated with quantitative measures. The present study is the first to evaluate the sleep quality of patients with chronic neck pain through the use of polysomnography. The study sought to identify the sleep characteristics of patients with chronic neck pain and then to determine whether these characteristics were associated with the severity of their neck pain. Laboratory testing with polysomnography was carried out on 32 males who had complaints of chronic neck pain and on 12 healthy participants who served as controls. Compared to the control subjects, patients with chronic neck pain were found to have significantly shorter times spent in sleep ( p  = 0.015), longer latencies to sleep onset ( p  = 0.015) and rapid eye movement (REM) sleep ( p  < 0.05), longer durations spent in Stage 1 ( p  < 0.05), and shorter durations spent in both Stage 2 ( p  = 0.001) and REM sleep ( p  = 0.00). The severity of discomfort was related negatively to the amount of time spent in REM sleep. The present study's quantitative measures corroborate the view that patients with chronic neck pain have poor sleep quality. These findings confirm long‐held clinical observations that the sleep quality of patients with chronic neck pain is compromised, and that, in this clinical group, poor sleep is at least a correlate of and may be an amplifier of perceived pain.